2010
DOI: 10.3354/meps08427
|View full text |Cite
|
Sign up to set email alerts
|

Near-bottom hydrodynamic effects on postlarval settlement in the American lobster Homarus americanus

Abstract: Following a planktonic larval phase, American lobster Homarus americanus postlarvae seek out appropriate habitat in which to settle and develop through a shelter-restricted juvenile phase. Previous studies have shown that lobster postlarvae exhibit strong directional swimming ability, distinct bottom-searching behaviours, and clear responses to physical and chemical cues at settlement. However, most laboratory experiments have been conducted in still water and little is known about how hydrodynamics affect lob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Orientation, habitat selection and settlement in response to physical and chemical stimuli have been demonstrated for larvae of a variety of taxonomic groups, and larvae likely integrate a suite of sensory cues at multiple spatial scales to successfully locate preferred settlement substrates [3], [7], [8]. Studies of larval invertebrate settlement cues have focused largely on chemical compounds [9], [10] and habitat characteristics, such as surface texture or near-bottom hydrodynamics [11][13], but these stimuli are only detectable by larvae that are in close proximity of the seafloor [7], [12]. While a combination of habitat characteristics, such as local flow patterns, chemical exudates, light intensity and substrate topography are used by benthic invertebrate larvae in small-scale habitat selection, it is still unclear how larvae effectively locate discrete patches of bottom settlement habitat as they disperse over kilometers, especially for species that are relatively weak swimmers compared to surrounding currents.…”
Section: Introductionmentioning
confidence: 99%
“…Orientation, habitat selection and settlement in response to physical and chemical stimuli have been demonstrated for larvae of a variety of taxonomic groups, and larvae likely integrate a suite of sensory cues at multiple spatial scales to successfully locate preferred settlement substrates [3], [7], [8]. Studies of larval invertebrate settlement cues have focused largely on chemical compounds [9], [10] and habitat characteristics, such as surface texture or near-bottom hydrodynamics [11][13], but these stimuli are only detectable by larvae that are in close proximity of the seafloor [7], [12]. While a combination of habitat characteristics, such as local flow patterns, chemical exudates, light intensity and substrate topography are used by benthic invertebrate larvae in small-scale habitat selection, it is still unclear how larvae effectively locate discrete patches of bottom settlement habitat as they disperse over kilometers, especially for species that are relatively weak swimmers compared to surrounding currents.…”
Section: Introductionmentioning
confidence: 99%
“…Lobster settlement behavior may be affected by spatial and temporal differences in oceanographic conditions, such as flow and water mass temperature (Lillis and Snelgrove, ; Annis et al ., ) and should, therefore, be considered when examining and predicting settlement patterns. Moreover, water masses encountered by larvae may influence their growth and survival through temperature‐mediated effects (Cowen and Sponaugle, ).…”
Section: Discussionmentioning
confidence: 99%
“…Environmental conditions, including physical, chemical, and biological factors in natural habitats, highly determine the recruitment rates of lobster larvae (Keulder 2005). Several authors have previously reported the physical and chemical characteristics of the natural 1643 settlement areas of lobster larvae (Amin et al 2022b;Boudreau et al 1992;Lillis and Snelgrove 2010). However, studies investigating biological aspects of settlement habitat in the natural environment of lobster larvae are very limited.…”
Section: Introductionmentioning
confidence: 99%